The Effect of Perceived Organizational Support on Intention to Stay Mediated by Employee Engagement and Job Satisfaction - Pithaloka, Dyah Ayu; Ardiyanti, Niken (Jurnal Aplikasi Manajemen, 2024)
Employees have an important role in a business. Employees are human resources employed by companies who play the role of planners, executors, and drivers in determining the performance and sustainability of the company. Organizational support for employees can be an important factor in retaining employees in the company. The main objective of this study was to determine the perceptions of employee organizational support, employee engagement, and the level of job satisfaction on the employee's intention to stay with the organization. The dataset was generated through a quantitative survey of 233 respondents at PT. Yodya Karya (Persero) from March to April 2023, and analyzed using Structural Equation Modelling (SEM). The findings of this research are that there is no significant and positive direct influence between perceived organizational support on employees' intentions to stay at the company, but rather that perceived organizational support has an impact when there are other things that influence employees' intentions to stay at the company through job satisfaction. Job satisfaction also has a big influence on employees' intentions to stay at the company and employee involvement in the company. Thus, Job Satisfaction at the company needs to be increased to increase employee intentions to stay at the company and also Employee Engagement. Therefore, from the results of this research can be seen that Job Satisfaction becomes an important variable in mediating the influence of Perceived Organizational Support and Intention to Stay.